2012
DOI: 10.4171/ggd/150
|View full text |Cite
|
Sign up to set email alerts
|

Free products, orbit equivalence and measure equivalence rigidity

Abstract: We study the analogue in orbit equivalence of free product decomposition and free indecomposability for countable groups. We introduce the (orbit equivalence invariant) notion of freely indecomposable (FI) standard probability measure preserving equivalence relations and establish a criterion to check it, namely non-hyperfiniteness and vanishing of the first L 2 -Betti number. We obtain Bass-Serre rigidity results, i.e. forms of uniqueness in free product decompositions of equivalence relations with (FI) compo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Further he showed that, given two stably orbit equivalent actions, σ and ρ, of such groups with σ | Γ and ρ| Λ ergodic, one has σ | Γ and ρ| Λ are stably orbit equivalent. He was also able to prove a similar measure equivalence rigidity for certain classes of direct products and amalgamated free products, thus obtaining rigidity results á la Monod and Shalom [20], as well as of Bass-Serre type [16,1,2]. His methods rely on Ozawa's techniques [23,24] involving the class S of groups, being C * -algebraic in nature and depending crucially on exactness of the groups involved.…”
Section: Oe-rigidity Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Further he showed that, given two stably orbit equivalent actions, σ and ρ, of such groups with σ | Γ and ρ| Λ ergodic, one has σ | Γ and ρ| Λ are stably orbit equivalent. He was also able to prove a similar measure equivalence rigidity for certain classes of direct products and amalgamated free products, thus obtaining rigidity results á la Monod and Shalom [20], as well as of Bass-Serre type [16,1,2]. His methods rely on Ozawa's techniques [23,24] involving the class S of groups, being C * -algebraic in nature and depending crucially on exactness of the groups involved.…”
Section: Oe-rigidity Resultsmentioning
confidence: 96%
“…So let us assume that θ t does not converge uniformly on (P ) 1 . Therefore by transversality of θ t , Theorem 1.1, one can find a constant 0 < c < 1, and infinite sequences t k ∈ R, u k ∈ U (P ) such that t k → 0 and θ t k (u k ) − E M θ t k (u k ) 2 c.…”
Section: W * -Rigidity Resultsmentioning
confidence: 99%
See 3 more Smart Citations